The Newest Offering in the Higher Education Leadership Movement: A Model Campus-Wide Residential Program for Faculty and Staff . - Susan M. Scott; Mary Hale Tolar (Educational Considerations, 2009)
The purpose of this article is to review the recent emphases by institutions of higher education on leadership development and to describe a model program for a population not yet widely addressed: faculty and staff.
Keywords: leadership; development; movement; program; literature; review; experience; feedback; participant; evaluation; data